An analysis on the effect of computer self-efficacy over scientific research self-efficacy and information literacy self-efficacy - Tuncer, Murat (My University, 2013)
Present research investigates reciprocal relations amidst computer self-efficacy, scientific research and information literacy self-efficacy. Research findings have demonstrated that according to standardized regression coefficients, computer self-efficacy has a positive effect on information literacy self-efficacy. Likewise it has been detected that information literacy self-efficacy positively affects scientific research self-efficacy. It has also been designated that computer self-efficacy has a positive impact on scientific research self-efficacy. It is suggested that the findings of present research shall provide assistance in detecting the sequence of computer, information literacy and scientific research skills development courses that shall be integrated into curriculums.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Computer self-efficacy; İnformation literacy self-efficacy; Scientific research self-efficacy; Teacher training; Teaching and learning